Strengthening local government capacity: Assistance in the preparation of the 2024 LP2KD for Central Buton Regency - Satria, Eko; Wijaya, Andy Arya Maulana; Suherman, Ansar; Sya’ban, La Ode Muhammad Azhar; Maulana, Harry Fajar; Adwian, Angga (Universitas Muhammadiyah Magelang, 2025)
Poverty remains a significant and persistent challenge for Central Buton Regency, with various issues hindering the effectiveness of poverty reduction programs. This activity aimed to assist the Government of Central Buton Regency in preparing the 2024 Regional Poverty Reduction Implementation Report (LP2KD), as mandated by Presidential Instruction of the Republic of Indonesia Number 4 of 2022 and Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 53 of 2020. The implementation method involved initial coordination (kick-off meeting), observation of data needs, and Focused Group Discussions (FGD) with Regional Apparatus Organizations (OPD) to identify the root causes of poverty. The main outcome of this activity was the completion of the 2024 Regional Poverty Reduction Implementation Report (LP2KD) for Central Buton Regency. This report presents a comprehensive analysis of poverty conditions, identifies existing problems, and provides practical recommendations for the formulation of more effective and targeted poverty reduction policies.